2013
DOI: 10.2138/am.2013.4384
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and X-ray diffraction investigation of the behavior of hanksite and tychite at high pressures, and a model for the compressibility of sulfate minerals

Abstract: The rare evaporite minerals hanksite, Na 22 K(SO 4 ) 9 (CO 3 ) 2 Cl, and tychite, Na 6 Mg 2 (CO 3 ) 4 (SO 4 ), are excellent case studies for the high-pressure behavior of ionic groups since their structures combine ionic complexity and high symmetry (hexagonal P6 3 /m and cubic Fd3, respectively). Here we investigate the structure and compressibility of hanksite up to 20 GPa in the diamond-anvil cell using Raman spectroscopy and X-ray diffraction and of tychite up to 17 GPa in the diamond cell using X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…3a) coincided with literature data obtained for tychite. 25,40,41 Fig. 3b shows the FTIR spectrum of prepared Na 6 Mg 2 (CO 3 ) 4 SO 4 .…”
Section: Papermentioning
confidence: 99%
“…3a) coincided with literature data obtained for tychite. 25,40,41 Fig. 3b shows the FTIR spectrum of prepared Na 6 Mg 2 (CO 3 ) 4 SO 4 .…”
Section: Papermentioning
confidence: 99%
“…The crystal structure of ferrotychite was refined by Malinovskii et al [18]. Spectroscopic properties of the northupite-group minerals have been studied in a number of works [17,19]. In the most recent work, Sidorov et al [20] reported Raman spectra for tychite, manganotychite, and ferrotychite.…”
Section: Introductionmentioning
confidence: 99%